Unravelling the nucleation and growth of 11-2¯2 twins. (1st July 2022) - Ostapovets, Andriy; Verma, Ritu; Serra, Anna
Highlights: The nucleation and growth of 11 2 ¯ 2 twin is connected to the stability of ω-phase. 11 2 ¯ 2 twin is nucleated by double α-ω-α phase transformation. The migration of the twin boundary is mediated by the glide of pairs of steps. Gliding of 2 steps convert boundary's configuration into ω-phase and back to α-phase. The pair of steps, with ω-phase in between, is a dissociated b 3/3 disconnection. Abstract: A recently proposed mechanism of 11 2 ¯ 2 twin nucleation in Ti by reverse phase transformation is analysed. It is demonstrated that, not only nucleation, but also growth mechanism of an already formed twin is connected to the possibility of the phase transformation in the system, which leads to the existence of several competing structures of twin boundary. The twin growth is mediated by subsequent glide of step-like defects (disconnections) along the 11 2 ¯ 2 boundary. The twin shear is completed by gliding of pair of disconnections, which also converts twin boundary structure between two alternative variants. Graphical abstract: Image, graphical abstract .